2023
DOI: 10.1002/1878-0261.13442
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic cancer‐derived small extracellular vesical ezrin activates fibroblasts to exacerbate cancer metastasis through STAT3 and YAP‐1 signaling pathways

Abstract: Cancer‐associated fibroblasts (CAFs), a major component of the tumor microenvironment (TME) in pancreatic ductal adenocarcinoma (PDAC), play an important role in tumorigenesis, metastasis, and chemoresistance. Tumor‐derived small extracellular vesicles (sEVs), which mediate cell‐to‐cell communication between cancer cells and fibroblasts, are also critical for cancer progression and metastasis. However, it remains unclear how PDAC cell‐derived sEVs activate fibroblasts, which contributes to tumor progression. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 94 publications
(106 reference statements)
0
2
0
Order By: Relevance
“…A study showed that exosomes derived from hypoxic PCCs by transferring miR-301a-3p to macrophages stimulate their polarization to M2 phenotype through the PTEN/PI3Kγ pathway ( 90 ). It has also been shown that exosomes derived from pancreatic tumor cells enriched with ezrin after inducing M2 polarization can increase tumor metastasis to the liver ( 91 ). On the other hand, when M2 macrophages are found in the tumor site, they can help tumor expansion by producing exosomes ( 92 ).…”
Section: Tumor-derived Exosomes In Pancreatic Cancer Progressionmentioning
confidence: 99%
“…A study showed that exosomes derived from hypoxic PCCs by transferring miR-301a-3p to macrophages stimulate their polarization to M2 phenotype through the PTEN/PI3Kγ pathway ( 90 ). It has also been shown that exosomes derived from pancreatic tumor cells enriched with ezrin after inducing M2 polarization can increase tumor metastasis to the liver ( 91 ). On the other hand, when M2 macrophages are found in the tumor site, they can help tumor expansion by producing exosomes ( 92 ).…”
Section: Tumor-derived Exosomes In Pancreatic Cancer Progressionmentioning
confidence: 99%
“…[61] In addition to KRAS, PCCs also transmitted exosomal Ezrin to TAMs and accelerated their M2 polarization. [62] Under hypoxia, PCCs secreted exosomal miR-301a-3p and promoted M2 polarization of TAMs as well through activating PTEN/PI3K signaling pathway. [63] However, PCCs transfected with miR-155 and miR-125b2 could release exosomes rich in these 2 microRNAs, transforming immunosuppressive M2 TAMs to M1 phenotype with anticancer properties.…”
Section: Pancreatic Cancer Cells–immune Cellsmentioning
confidence: 99%